STEAM pedagogy in foreign language education: An endeavour to broaden CLIL pedagogy through 6E’s framework - David Imamyartha; Utami Widiati; Aan Erlyana Fardhani; Alifiyah A’yunin; Mitasari Mitasari; Galuh Candraning Hapsari (Indonesian Journal of Applied Linguistics)
This study addressed the dilemma in Content and Language Integrated Learning (CLIL) teaching. It argued that a STEAM pedagogy (Science, Technology, Engineering, Arts, and Mathematics) can inform and broaden CLIL pedagogy through 6E’s framework (engage, explore, explain, engineer, enrich, and evaluate). The authors first theoretically highlighted how STEAM pedagogy addressed some of the issues concerning CLIL instruction and showed that 6E’s framework cohered with the 4C’s (culture, content, cognition, and communication) of pluriliteracies approach to CLIL. We then actuated this conceptualization through a case study exploring Indonesian EFL learners’ engagement in 16-meeting CLIL lessons by examining their multidimensional learning experiences, affectivity, and emotionality. Data were oriented to the contextual variables of effective learning from learners’ standpoint and collected through Academic Emotion Questionnaire (AEQ), language learning attitude battery, and reflection sheet distributed to 204 college learners in six CLIL classes with 6E’s framework. The findings demonstrated the potency of 6E’s framework to provide vital scaffolding for discipline-specific literacies through scientific inquiry in language learning. The framework stimulated intensive multidimensional learning, positive academic emotions, and positive attitudes toward CLIL lessons. Students’ reflections underscored how the framework paved engaging authentic language tasks and science projects as essential drives for intrinsic motivation to learn content and language despite limited linguistic repertoires.